Surface reconstruction on Ni2P@CC to form an ultrathin layer of Ni(OH)2 for enhancing the capture and catalytic conversion of polysulfides in lithium–sulfur batteries. Issue 7 (27th January 2023) - Peng, Lin; Qu, Meixiu; Sun, Rui; Yang, Weiwei; Wang, Zhenhua; Sun, Wang; Bai, Yu
Abstract : An ultrathin layer of Ni(OH)2 is in situ introduced to the Ni2 P surface by an electrochemical method to realize the regulation of surface properties of Ni2 P. The S/Ni(OH)2 –Ni2 P@CC based cell exhibits superior cycle stability and high areal capacity. Abstract : The shuttling behaviours and sluggish reaction kinetics of lithium polysulfides (LiPSs) are the main drawbacks that hinder the commercialization of lithium–sulfur (Li–S) batteries. Since electrochemical reactions mainly occur on the surface of electrocatalysts, regulating the surface properties of electrocatalysts is regarded as an effective strategy to address the above challenges. Herein, an ultrathin layer of Ni(OH)2 is introduced onto the surface of Ni2 P by an in situ electrochemical surface reconstruction strategy. Experimental investigations and theoretical calculations indicate that the introduced Ni(OH)2 surface layer can strengthen chemical immobilization toward LiPSs. In addition, the emerged ultrathin layer of Ni(OH)2 on Ni2 P@CC accelerates the LiPS conversion and Li2 S deposition. The derived S/Ni(OH)2 –Ni2 P@CC-based cell exhibits excellent cyclability over 200 cycles at 1C with a decay rate of 0.07% per cycle and a high capacity of 7.96 mA h cm −2 at a relatively high sulfur loading of 11.10 mg cm −2 . This work provides an insight into the design of high-performance Li–S batteries through a surface reconstruction strategy.